Comprehensive population-based survey of migraine in Japan: results of the ObserVational Survey of the Epidemiology, tReatment, and Care Of MigrainE (OVERCOME [Japan]) study. (2nd November 2021) - Hirata, Koichi; Ueda, Kaname; Komori, Mika; Zagar, Anthony J.; Selzler, Katherine J.; Nelson, Ann Marie; Han, Yimei; Jaffe, Dena H.; Matsumori, Yasuhiko; Takeshima, Takao
Abstract: Objective: The ObserVational survey of the Epidemiology, tReatment, and Care Of MigrainE study in Japan (OVERCOME [Japan]) aimed to provide an up-to-date assessment of migraine epidemiology in Japan. Methods: OVERCOME (Japan) was a cross-sectional, population-based web survey of Japanese adults recruited from consumer panels. People with active migraine (met modified International Classification of Headache Disorders, 3rd edition [ICHD-3] criteria or had a self-reported physician diagnosis of migraine) answered questions about headache features, physician consultation patterns, and migraine medication use. The burden and impact of migraine were assessed using Migraine Disability Assessment (MIDAS) and Work Productivity and Activity Impairment scales. Results: In total, 231, 747 respondents accessed the screener, provided consent, and were eligible for the survey. The migraine group included 17, 071 respondents (mean ± SD age 40.7 ± 13.0 years; 66.5% female). ICHD-3 migraine criteria were met by 14, 033 (82.2%) respondents; 9667 (56.6%) self-reported a physician diagnosis of migraine. The mean number of monthly headache days was 4.5 ± 5.7 and pain severity (0–10 scale) was 5.1 ± 2.2. In the migraine group, 20.7% experienced moderate to severe migraine-related disability (MIDAS score ≥ 11). Work productivity loss was 36.2% of work time missed, including 34.3% presenteeism. Only 57.4% of respondents had ever sought medical care for migraine/severe headache. Most respondents (75.2%) were currently using over-the-counter medications for migraine; 36.7% were using prescription nonsteroidal anti-inflammatory drugs, and only 14.8% were using triptans. Very few (9.2%) used preventive medications. Conclusions: Unmet needs for migraine health care among people with migraine in Japan include low rates of seeking care and suboptimal treatment.